Autoria: as injunções do jogo significante - Santos, Maria Aparecida dos (2015)
This thesis retakes the issue of authorship, discussed in the text of Michel Foucault ([1969] 2002), "What is an author?" The aim is to (re)put the issue of authorship from another angle, not determined only by the imaginary vertex, where the author is situated as the origin of his act. Foucault, albeit in another position, discussing the author's notion undermines the identification/strict linkage and traditional between author and individual proposing the authorfunction for inspecting relationship between the author and the text. For that, it considered that the statement of indifference is an immanent rule of contemporary writing. A writing that, according to Foucault, is not obliged with an interiority, since it's "set of signs headed fewer by its content meaning that by nature itself of the signifier" (Foucault, [1969] 2002). Two reasons explored in this thesis delimit the meaning of "indifference" in Foucault's work: (1) the writing has freed up to connecting to a subjective expression - it only refers to itself; (2) the writing is related to the death. To observe the operation of this set of signs, when discussing authorship, parts it from the reading language while system described by Saussure ([1916] 2006), seeking to raise: (1) "as Foucault articulates the relation with the exterior of speech and language that only knows its own order (laws of internal reference of the language)" ?; (2) How relates set of signs and the nature of the signifier? and (3) "the Saussurian concept of the language, defined as" value system "is present in Foucault's discussion of the authorship?". The answers to these questions were related to the theoretical framework established by the Research Group Acquisition, disease and clinical language (LAEL-Derdic / CNPq), that Prof. Dra. Maria Francisca Lier-DeVitto and Prof. Dra. Lucia Arantes are coordinators. The importance attributed to there to its own language and the significant allowed a differentiated reading with respect to Foucault's discussions, second a target other than represented a return to Saussure (MILNER, 2002) in the 1980s. The nature of significant pointed to constitutive tensions and to a faulty connection in the articulation of a work or a text to a subject - there is non-coincidence of the subject with himself, and also non-coincidence of him with his writing. The focus on significant (and not in the meaning), where there is an emphasis on laws of internal reference of language (and not in the discursive externality), demanded differences from the discussion of the issue of authorship, indicating advances and limitations in its questioning by the philosopher